Novel pathways involved in nephrotoxicity induced damage and recovery - Li, Yihe (2020)
Acute kidney injury (AKI) has become a rising global concern affecting over 13 million people every year and one of the main causes is nephrotoxic drugs-induced AKI. Understanding the mechanisms of which and the genetic pathway involved during damage and recovery enable further investigation on targeted treatments. Therefore, the overall aim of this study was to investigate the key genes or pathways involved in nephrotoxic drug-induced damage and recovery, thus help understanding further the paths of damage and potential recovery in nephrotoxic injury.